IMPLICATIONS OF INTERNATIONAL REFUGEE LAW FOR INDONESIAN CITIZENS FACING POLITICAL EXILE - Nasution, M. Ghopar Azizi; Rosmawati, Rosmawati (Universitas Syiah Kuala, 2024)
The 1951 Refugee Convention and the 1967 Refugee Protocol provide a clear foundation for understanding the status and citizenship rights of international refugees. This article explains the position of political exiles from the perspective of international refugee law and examines the process of seeking asylum for those in exile. Drawing on normative juridical research, this article analyzes data from various legal sources to shed light on this issue. Political exiles can be categorized as international refugees because they leave their country not by personal choice, but due to differences in political views that threaten their lives. The process of resolving asylum claims involves filing an application with the host country, followed by an assessment and examination of eligibility for refugee status. It is essential that receiving countries adhere to their international legal obligations, including the 1951 Refugee Convention and the 1967 Refugee Protocol, when handling cases of political exile.